Efektivitas Model Pembelajaran Joyful Learning pada Pembelajaran Aksara Jawa dalam Pendekatan Kuantitatif - Anwar, Adhitya Tegar Pratama; Sukoyo, Joko (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
The use of Javanese script is increasingly being replaced by the Latin alphabet, and while preservation efforts through school-based learning have been implemented, they remain ineffective due to monotonous instructional methods. This study examines the effectiveness of an innovative approach to overcoming the monotony in Javanese script learning through a joyful learning model incorporating e-flashcards and engklek games. The research design involves two class groups: an experimental group, which receives the joyful learning treatment, and a control group, which undergoes conventional instruction. Quantitative data were collected from a total sample of 66 students through a practical reading test of Javanese sentences conducted after the treatment. The data were then analyzed using hypothesis testing, revealing that the joyful learning model significantly enhances learning outcomes. Based on these findings, it can be concluded that the joyful learning model serves as an effective alternative for teaching Javanese script, offering a more engaging and interactive approach to script preservation and literacy development.